2011
DOI: 10.2174/157015911795017254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MDMA on Extracellular Dopamine and Serotonin Levels in Mice Lacking Dopamine and/or Serotonin Transporters

Abstract: 3,4-Methylendioxymethamphetamine (MDMA) has both stimulatory and hallucinogenic properties which make its psychoactive effects unique and different from those of typical psychostimulant and hallucinogenic agents. The present study investigated the effects of MDMA on extracellular dopamine (DAex) and serotonin (5-HTex) levels in the striatum and prefrontal cortex (PFC) using in vivo microdialysis techniques in mice lacking DA transporters (DAT) and/or 5-HT transporters (SERT). subcutaneous injection of MDMA (3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 31 publications
4
39
0
1
Order By: Relevance
“…Microdialysis studies have shown an increase in synaptic DA and serotonin in the nucleus accumbens following exposure to MDMA, similarly to that seen with other addictive drugs (Cadoni et al, 2005;Colussi-Mas et al, 2010;Gudelsky and Yamamoto, 2008). A recent study has demonstrated the involvement of serotonin and DA transporters (SERT and DAT, respectively) in MDMA-induced DA release in the striatum, finding it to be blocked only in mice lacking both transporters, but not in those lacking either DAT or SERT (Hagino et al, 2011). In this way, disruption of DA and/or 5-HT neurotransmission impedes animals from experiencing the reinforcing effect of MDMA.…”
Section: Discussionmentioning
confidence: 84%
“…Microdialysis studies have shown an increase in synaptic DA and serotonin in the nucleus accumbens following exposure to MDMA, similarly to that seen with other addictive drugs (Cadoni et al, 2005;Colussi-Mas et al, 2010;Gudelsky and Yamamoto, 2008). A recent study has demonstrated the involvement of serotonin and DA transporters (SERT and DAT, respectively) in MDMA-induced DA release in the striatum, finding it to be blocked only in mice lacking both transporters, but not in those lacking either DAT or SERT (Hagino et al, 2011). In this way, disruption of DA and/or 5-HT neurotransmission impedes animals from experiencing the reinforcing effect of MDMA.…”
Section: Discussionmentioning
confidence: 84%
“…An established mechanism of MDMA- induced toxicity in the brain is an increase of extracellular 5-HT and DA levels via action on SERT and DAT both in vitro [5760] and in vivo [61] with higher affinity binding to SERT [27]. MDMA also inhibits the enzyme monoamine oxidase [15] responsible for inactivation of serotonin and dopamine [62] that contributes to their elevated levels.…”
Section: Discussionmentioning
confidence: 99%
“…The locomotor stimulant effects of MDMA are abolished in SERT KO mice (Bengel, et al, 1998), as is MDMA-induced serotonin release and MDMA self-administration (Trigo, et al, 2007). Surprisingly, and perhaps indicating non-SERT mediated mechanisms in some of the effects of MDMA, increases in extracellular dopamine levels in the nucleus accumbens in SERT KO mice after administration of MDMA are unchanged (Trigo, et al, 2007) or reduced (Hagino, et al, 2011). In the latter study, the effects of MDMA on dopamine release were only eliminated in combined DAT/SERT KO mice.…”
Section: Modeling Candidate Genes With Knockout (Ko) Micementioning
confidence: 98%